Pasensya na - Lampa, Vincent Mark Ong 1984- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2006)
"The filmmakers believe that prostitution is, for the most part, seen in a negative light by our predominantly Catholic society. As such, people involved in the flesh trade are then shunned by society and are prejudged, not even given the chance to tell their stories first. They believe that prostitution is something that is not immoral. Forcing someone, at the threat of life or property, into prostitution is immoral, but prostitution itself is devoid of any immorality. It's even a preference for others. They also believe that love is something more than the ideal notion we grew up listening to. "Love makes the world go round" and such are quotes we have grown accustomed to, hence it is ingrained in our consciousness. But love is something much more complex than that. The filmmakers believe that love will always be subject to people's priorities in life. It will NOT keep one alive. This thesis documents the production of a fifteen-minute narrative video production, Pasensiya Na. In addition, the script, storyboard, and budget are included. Written and directed by Vincent Mark Lampa and Ana Katrina Reyes, Pasensiya Na is a story that follows Susan, a prostitute, as he works and unqittingly searches for love in the men she meets. She later finds out that love is not enough to make one happy. This story involves the harsh reality of relationships and people's priorities in life. The film was shot in three days in Quezon City using a mini-DV camera and halogens and PAR-38s for lighting."
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman